Developing a textbook to support pharmacy students' mathematical problem-solving skills - Savitri, Fitri; Sabrina, Alifa; Tuahuns, Farida (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2025)
Mathematics is a vital tool for solving problems in everyday life. For pharmacy students, it is the basis for formulating pharmaceutical preparations, calculating maximum doses, and performing dilutions. In calculations, students must understand the problem, plan the solution, carry out the steps, and ensure accuracy, which reflects problem-solving ability. There are four books with ISBNs, 3 discussing only mathematical concepts and one focusing on pharmaceutical calculations, but none combining both. Therefore, it is urgent to develop contextual, problem-solving-based textbooks to support pharmaceutical mathematics learning. This study aims to create a pharmaceutical mathematics textbook that strengthens problem-solving skills, particularly in measurement units and concentration statements. This study employed the ADDIE development model with 95 first-year pharmacy diploma students as respondents, and data were collected through a questionnaire. The results of the validity test, as evaluated by material and media experts, averaged 85.98% (considered very valid), while the feasibility test, conducted by lecturers and students, averaged 84.55% (also considered very feasible). It can be concluded that the developed textbook is valid, practical and effective for use in diploma and undergraduate pharmacy programs. The results can also guide the development of other chapters in pharmaceutical mathematics and help evaluate teaching materials to improve problem-solving skills at STIKes IKIFA.